2008
DOI: 10.1016/j.smim.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific immunotherapy targeting the EGFRvIII mutation in patients with malignant glioma

Abstract: Conventional therapies for malignant gliomas (MGs) fail to target tumor cells exclusively, such that their efficacy is ultimately limited by non-specific toxicity. Immunologic targeting of tumor-specific gene mutations, however, may allow more precise eradication of neoplastic cells.The epidermal growth factor receptor variant III (EGFRvIII) is a consistent tumor-specific mutation that is widely expressed in MGs and other neoplasms. This mutation encodes a constitutively active tyrosine kinase that enhances tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
132
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 143 publications
(153 reference statements)
1
132
0
Order By: Relevance
“…On the basis of these observations, we extended our study to assess the role of SIRPa1 receptor on tumor cell migration mediated by the constitutively active EGFRvIII oncoprotein. Enhanced migration mediated by EGFRvIII has been observed in many cell types (Pedersen et al, 2004;Sampson et al, 2008) and neural stem cells (Boockvar et al, 2003(Boockvar et al, , 2005. Interestingly, SIRPa1-overexpressing U87MG.EGFRvIII cells exhibited reduced migration in a transwell chamber migration assay, when compared with EV control cells (Figure 2).…”
Section: Sirpa1 Overexpression Downmodulates Egfrviiimediated Migratimentioning
confidence: 94%
“…On the basis of these observations, we extended our study to assess the role of SIRPa1 receptor on tumor cell migration mediated by the constitutively active EGFRvIII oncoprotein. Enhanced migration mediated by EGFRvIII has been observed in many cell types (Pedersen et al, 2004;Sampson et al, 2008) and neural stem cells (Boockvar et al, 2003(Boockvar et al, , 2005. Interestingly, SIRPa1-overexpressing U87MG.EGFRvIII cells exhibited reduced migration in a transwell chamber migration assay, when compared with EV control cells (Figure 2).…”
Section: Sirpa1 Overexpression Downmodulates Egfrviiimediated Migratimentioning
confidence: 94%
“…Since mutant versions of EGFR are frequently found in GBM tumors, specific peptides contained in EGFR mutations have been investigated for use in vaccines (10,11). However, a number of significant challenges remain.…”
Section: Introductionmentioning
confidence: 99%
“…TAAs associated with glioblastomas have been described and include epidermal growth factor receptor vIII, interleukin-13Ra2 (IL-13Ra2), IL-4, Wilms' tumor 1 (WT1), survivin, and erythropoietin-producing hepatocellular receptor tyrosine kinase class A2 (EphA2). 13,33,35 These studies, however, have shown limited clinical efficacy.…”
mentioning
confidence: 99%